2017
DOI: 10.3855/jidc.8169
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Trypanosoma Cruzi antibodies in blood donors from the Sao Paulo State, Brazil, between 2012 and 2014

Abstract: Introduction: American tripanosomiasis (Chagas disease), the second most neglected disease in the world, is caused by the protozoan parasite Trypanosoma cruzi. Though natural transmission by insect vectors has been controlled, there is significant risk of T. cruzi transmission by blood transfusion in non-endemic regions, generally due to immigration processes from endemic areas. Methodology: The objective of this study was to evaluate anti-T. cruzi seroprevalence in blood donors from the western part of São Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
1
7
0
1
Order By: Relevance
“…The seroprevalence of T. cruzi infection was higher in individuals aged 30 years or older and individuals with 12 years or less of education in the first and second screening, and seroprevalence was significantly higher in men in the first screening. These results agree with previous studies [21][22][23][24][25] . Data on seroprevalence rates according to marital status and racial group are summarized in Table 1.…”
Section: /7supporting
confidence: 94%
See 2 more Smart Citations
“…The seroprevalence of T. cruzi infection was higher in individuals aged 30 years or older and individuals with 12 years or less of education in the first and second screening, and seroprevalence was significantly higher in men in the first screening. These results agree with previous studies [21][22][23][24][25] . Data on seroprevalence rates according to marital status and racial group are summarized in Table 1.…”
Section: /7supporting
confidence: 94%
“…Previous studies with blood donors reported that the percentage of non-negative results was higher among married individuals, people in stable relationships 7 , and subjects with lower education levels 21 . The percentage of infection was higher in men [22][23][24][25] , although one study found that the rate was higher in women 21 . The number of cases was higher in older age groups, especially in individuals older than 30 years 7,22,23,25,26 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this modern time, diaspora has been an effective vehicle in spreading this infection to different parts of the world. While other modes of infections have also been identified from ingesting contaminated food or drinks with the feces of the kissing bug [5] to blood transfusions [6], and organ transplantation [7,8] as being incidental causes of parasite transmission.…”
Section: Transmission: a Wide Spectrum Of Dissemination Modes?mentioning
confidence: 99%
“…The etiological agent of Chagas disease, Trypanosoma cruzi, destroys the nerve plexuses of the esophageal wall, which results in reduced peristalsis and a hypertonic lower esophageal sphincter, causing achalasia (absence of peristaltic movements in the esophagus and narrowing of the cardia) and megaesophagus (dilatation of the esophagus) [3]. The main symptoms of megaesophagus are dysphagia, bronchoaspiration of regurgitated food, weight loss, vomiting, excessive salivation, retrosternal pain, and heartburn.…”
Section: Introductionmentioning
confidence: 99%